2016
DOI: 10.1007/s10661-016-5574-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, respiratory, and total mortality attributed to PM2.5 in Mashhad, Iran

Abstract: Poor air quality is one of the most important environmental problems in many large cities of the world, which can cause a wide range of acute and chronic health effects, including partial physiological disorders and cardiac death due to respiratory and cardiovascular diseases. According to the latest edition of the national standard for air quality, maximum contamination level is 15 μg/m(3) per year and 35 μg/m(3) per day. The aim of this study was to evaluate cardiovascular, respiratory, and total mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Due to its small diameter and large surface area, PM with an aerodynamic diameter less than 2.5 μM (PM 2.5 ) carries various toxic components and pathogens into the body and causes harm [2]. Many studies have indicated that there is a close association between mortality and PM 2.5 level, especially respiratory and cardiovascular mortality [3], [4], [5], [6]. As the site for gas exchange and a barrier from the external environment, the respiratory system is exposed directly to high levels of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its small diameter and large surface area, PM with an aerodynamic diameter less than 2.5 μM (PM 2.5 ) carries various toxic components and pathogens into the body and causes harm [2]. Many studies have indicated that there is a close association between mortality and PM 2.5 level, especially respiratory and cardiovascular mortality [3], [4], [5], [6]. As the site for gas exchange and a barrier from the external environment, the respiratory system is exposed directly to high levels of PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…The following list is not inclusive of all current air pollution agents; however, they are those that are targeted for reduction by the WHO, which include PM, ozone (O 3 ), nitrogen dioxide (NO 2 ) and sulfur dioxide (SO 2 ). Many air pollutants have been identified as health hazards, leading to negative health effects such as increased risk for cardiovascular diseases, and depressive symptomatology (27,28). As such, the aforementioned agents are key targets according to the air quality guidelines, as lowering their levels could help lower the associated burden of disease (29).…”
Section: Components Of Air Pollutionmentioning
confidence: 99%
“…Data collected in 2012 by the World Health Organization (WHO) (1) estimates that suicide accounts for 1.4% of deaths globally and is ranked as the second leading cause of death among individuals aged [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Consequently, the WHO has made efforts to reduce these rates by identifying and implementing preventative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…8,12,13 Many health assessment studies showed an association between ambient PM 2.5 levels and their impacts on cardio-respiratory mortality. [14][15][16][17][18] A long-term exposure to ambient PM 2.5 can cause deaths for ischemic heart diseases and chronic obstructive pulmonary diseases. 19,20 The ischemic heart diseases (IHD) is a cardiovascular condition characterized by inability of cardiac muscles to function effectively due to poor blood circulation caused by atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%